CO2 Inflow and Elements Desorption Prior to a Seismic Sequence, Amatrice‐Norcia 2016, Italy. (16th May 2019) - Boschetti, T.; Barbieri, M.; Barberio, M. D.; Billi, A.; Franchini, S.; Petitta, M.
Abstract: The 2016 Mw ≥ 6.0 Amatrice‐Norcia earthquakes (central Apennines, Italy) and the related seismic sequence were associated with increases in arsenic and vanadium concentrations recorded in groundwater springs a few months before the earthquakes occurred. To evaluate these signals as reliable seismic precursors and effective predictive tools, we studied the geochemical processes that caused these anomalies. Using chemical and isotope models, we show that increased concentrations of arsenic and vanadium, a slight increase in boron concentrations, and a concomitant lowering of the boron isotope ratio may be due to mineral desorption (e.g., from iron oxides and/or clays). We argue that a displacing effect on the trace elements sorbed on minerals was triggered by an excess of deep CO2 in groundwater, which occurred prior to the main seismic event as a result of preseismic crustal dilation. Our observations confirm the pivotal role of CO2 in the release of trace elements by alteration of solid phases and provide a new understanding of earthquake‐related water chemical anomalies. Key Points: Geochemical processes behind water anomalies prior to the 2016 earthquakes in Italy are investigated by chemical models Increased concentrations of As and V, a slight B increase, and a concomitant lowering of B isotope ratio occurred due to mineral desorption Desorption was triggered by an excess of deep CO2 in groundwater, which occurred prior to the mainshock due to preseismic crustal dilation